Pengaruh Usia dalam Kepemimpinan Transformasional dan Keterikatan Kerja pada Perusahaan - Sukmarani Sukmarani (Journal of Management and Bussines (JOMB), 2022)
This study aims to determine the relationship between transformational leadership with work engagement on employees in company X at the age as a control subject. This research method is quantitative research. The research subjects were 56 people who were selected by non-probability sampling technique, saturated sampling. Work engagement and transformational leadership are measured using a work engagement scale called UWES-17 which consists of 17 items and a transformational leadership scale. Correlation test with partial correlation technique was used to analyze SPSS 16.0 for Windows. The results showed that there was a positive and significant relationship between transformational leadership and control of work engagement according to age with a value of r = 0.407, p = 0.002 (p < 0.05). In conclusion, work engagement and transformational leadership of Company X are high. Most aspects of transformational leadership are related to this aspect of work engagement. The correlation between transformational leadership and job involvement is influenced by various factors such as age and gender. Keywords: Transformational Leadership, Job Engagement, Perception